ORAL CANDIDA ALBICANS COLONIZATION RATE IN FIXED ORTHODONTICS PATIENTS - Al-deen, Hussein Mohammad Shoga; Obeyah, Ahmed Ali; Al-Shamahy, Hassan Abdulwahab; Al-Shami, Ibrahim Zaid; AL-amri, Manal Ahmad Saleh; Al-labani, Mohammed A (Universal Journal of Pharmaceutical Research, 2020)
Objectives: The objective of this study was to assess the oral Candida albicans colonization ( OCAC) in a cluster of teenagers and young adults while being treated with a fixed orthodontic appliance (FOA). Subjects and methods: The investigational group was selected from orthodontic patients whom were examined clinically as soon as to get baseline information before active treatment. The cluster included 210 patients; 45 males, 165 females (mean age 21.6 ± 4.5 years). Clinical, demographic data and risk factors were collected in standard questionnaire then each individual was directed to carry out oral wash by a phosphate-buffered saline solution, which was expectorated and processed intended for the isolation of Candida species on Sabouraud’s dextrose agar. The isolated Candida species were identifying by culturing on chromogenic Candida agar and notice species-specific colony natures. Results: The predominant Candida species isolated was C. albicans with OCAC rate equal to 13.8% extensively enhanced after the insertion of a FOA, as revealed by the oral rinse (P < 0.05) techniques. The results also revealed an increase of OCAC in male patients (24.4%) than female patients (10.9%), 21-25 years patients (17.1%), and regular smoking and Qat chewing were significant associated risk factors (OR=28.6, OR=10.7 respectively , P < 0.0001). There was no significant association between C. albicans colonization with oral hygiene in fixed Orthodontic patients. Conclusion: As a whole, the current data suggest that the introduction of FOA is likely to promote OCAC. Moreover, it becomes visible that the routine oral hygiene procedures performed by these patients may not necessarily reduce OCAC while smoking and chewing Qat habits significantly increased OCAC in FOA. Also smoking and Qat chewing during FOA treatment should be banned if potential harmful effects are to be prevented. Further work with a larger sample size is required to confirm or deny these results. Peer Review History: Received 7 February 2020; Revised 15 March; Accepted 28 April; Available online 15 May 2020 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Dr. Tamer Mohamed Ali El Habibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg